Aviation, energy, exergy, sustainability, exergoenvironmental and thermoeconomic analyses of a turbojet engine fueled with jet fuel and biofuel used on a pilot trainer aircraft. (15th January 2023) - Balli, Ozgur; Caliskan, Nesrin; Caliskan, Hakan
Abstract: In this study, J69 military turbojet aero engine of Cessna T-37B/C pilot trainer aircraft fueled by jet fuel and %100-biofuel is assessed with aviation, energy, exergy, sustainability, exergoenvironment and thermoeconomic perspectives to show the reliability of the biofuel in terms of various aspects. The methyl-oleate ( C 19 H 36 O 2 ) is selected as a model substance for biodiesel for this study, because it is similar to the C:H:O ratio of the commercial biodiesel. J69 turbojet engine's exergy efficiency increases from 17.058% to 17.103% by using biofuel instead of jet fuel. J69 engine's environmental effect factor rises from 5.261 to 5.299 by the utilization of biofuel. Sustainability index reduces 1.463% for the combustion chamber component, 1.201% for the gas turbine component and 0.735% for the overall J69 engine by using biofuel instead of jet fuel. Fuel cost rates of the jet fuel mode is found as 533.355 $/h, while this cost of the biofuel mode is determined to be 846.058 $/h for take-off operation mode. Thereby, fuel cost of biofuel is higher than jet fuel. Specific exergy cost of jet fuel is determined as 20.14 $/GJ, while it is found as 31.667 $/GJ for biofuel. Results of the biofuel and jet fuel modes are close to each other. Thus, biofuel can be considered as a sustainable aviation fuel for J69 military turbojet engine used on the Cessna T-37B/C pilot trainer aircraft. Highlights: New investigation of biofuel utilization in a new engine type is done. Aviation, economic, energy, exergy and exergoenvironmental modelling are done. Biofuel sustainability for the utilization in the aviation engine is assessed. 100%-Biofuel and jet fuel effects on the engine are compared.